PHONETICS IN DIGITAL MEDIA: IMPLICATIONS FOR SPEECH RECOGNITION TECHNOLOGY - Attala Rania Insyra Pasaribu; Muhammad Miftah Al Khalili (Jurnal Recoms, 2024)
Phonetics, a branch of linguistics, examines the production, transmission, and perception of speech sounds, divided into articulatory, acoustic, and auditory subfields. Each area provides unique insights into how language sounds are generated, transmitted, and interpreted. This study explores the implications of phonetics in advancing digital speech recognition technology, particularly focusing on phoneme variation, intonation, and accent recognition. A research and development (R&D) methodology was employed, encompassing analysis, design, implementation, and evaluation stages to develop a prototype system integrating phonetic principles. The mixed-method approach combined qualitative and quantitative analyses to ensure a comprehensive evaluation of phonetics' integration in speech recognition technology. The research underscores the critical role of articulatory phonetics in modeling the production of diverse phonemes and accents, especially in complex languages like Arabic, which features unique phonemes such as pharyngeal sounds and emphatics. Findings reveal phonetics as foundational to developing inclusive and efficient Arabic speech recognition technology, with applications in language education, religious recitation, customer service, and linguistic research. This technology offers transformative potential for oral tradition preservation, inclusivity in services, and economic opportunities in the Arabic-speaking market, fostering accessibility and cultural preservation. The research highlights the interdisciplinary potential of phonetics to drive innovation, enhance social inclusion, and support the sustainable development of speech-based technologies in the digital era.